2018
DOI: 10.1371/journal.pone.0209434
|View full text |Cite
|
Sign up to set email alerts
|

Too soon to worry? Longitudinal examination of financial planning for retirement among Spanish aged workers

Abstract: The present study analyzes the relationship between three distal antecedents—financial literacy, confidence in retirement, and economic well-being—and financial planning for retirement evaluated at two different times. We used longitudinal data with repeated measures of financial planning for retirement obtained from a sample (N = 269) of active Spanish workers aged 45–62 years. The results confirm that self-perceived financial knowledge, confidence in retirement, and economic well-being are associated with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
0
11
0
2
Order By: Relevance
“…Appendix C presents how the included studies defined these two constructs. For instance, financial literacy involved skills for obtaining, understanding and applying financial concepts to facilitate better financial decisions/outcomes (Bavafa et al, 2019 ; Bennett et al, 2012 ; Gousia, 2016 ; James et al, 2018 ; Palací et al, 2018 ; Patel et al, 2016 ). This definition can be compared to health literacy, which posited that health‐related knowledge and skills could promote better healthcare decisions/outcomes (Bennett et al, 2012 ; Lamar et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Appendix C presents how the included studies defined these two constructs. For instance, financial literacy involved skills for obtaining, understanding and applying financial concepts to facilitate better financial decisions/outcomes (Bavafa et al, 2019 ; Bennett et al, 2012 ; Gousia, 2016 ; James et al, 2018 ; Palací et al, 2018 ; Patel et al, 2016 ). This definition can be compared to health literacy, which posited that health‐related knowledge and skills could promote better healthcare decisions/outcomes (Bennett et al, 2012 ; Lamar et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies confirmed the complementary relationships between the two concepts—financial literacy and health literacy. Financial literacy was related to increased retirement planning behaviours (Chambers et al, 2021 ; Palací et al, 2018 ; Topa et al, 2018 ); availing private long‐term care insurance (Gousia, 2016 ); obtaining additional health insurance other than government or employer‐provided insurance plans (Bavafa et al, 2019 ; Topa et al, 2018 ); and preventing delays or non‐fulfilment of therapeutic regimen due to costs (i.e. cost‐related nonadherence; Lamar et al, 2019 ; Patel et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, advice on financial plans through a financial expert (13,18,24,26,31,39,40,43,50,51,54) and collecting financial information (44) are among the factors measured in these studies.…”
Section: Preparation For Agingmentioning
confidence: 99%